Novel approaches in myelofibrosis - Steffen Koschmieder (HemaSphere)
Abstract Myelofibrosis (MF) is a clonal myeloid neoplasm characterized by bone marrow fibrosis, splenomegaly, and disease‐associated symptoms, as well as increased mortality, due to thrombosis, severe bleeding, infections, or progression to acute leukemia. Currently, the management of MF patients is tailored according to risk scores, with higher‐risk (intermediate‐2 and high‐risk) patients being assessed for allogeneic stem cell transplantation, which remains the only potentially curative treatment option. On the other hand, lower risk (low‐ and intermediate‐1 risk) patients who are symptomatic may be treated with JAK inhibitors or other drugs. However, none of these drug treatments have induced relevant rates of durable complete remissions, and, therefore, novel treatments are needed to improve the long‐term outcomes of MF patients. This review summarizes current preclinical and clinical approaches to MF therapy, including novel drug combinations involving JAK inhibitors and innovative monotherapies. These drugs target transcription, nuclear export, survival pathways, or various intracellular pathways, ranging from JAK‐STAT signaling to PI3‐Kinase, TP53, PIM1, or S100A8/A9/toll‐like receptor pathways. Also, extracellular targeting using interferon, calreticulin mutant‐specific antibodies, and other immunotherapeutic approaches are discussed, as well as various antifibrotic strategies. In addition, preclinical approaches that target individual mutated clones, for example, by mutation‐specific JAK2V617F inhibitors or DNA repair pathway inhibitors, are presented. Finally, current efforts of generating novel endpoints for clinical trials aim more at disease modification and overall survival than at improvements of splenomegaly or symptoms. Together, the new generations of clinical trials promise to offer substantial improvements in the management of MF patients and long‐term disease control.